CERVICAL HYDATID DISEASE - Anwar, Javed; Javed, Koukab; Parveen, Ishrat; ., Sanaullah (Pakistan Armed Forces Medical Journal, 2017)
A 24 years old female presented with complaints of neck pain and progressive paraparesis. Her MRI cervical spine showed multiple cystic lesions in prevertebral regions at C1 and C2 levels with extension into neural foramina bilaterally. This proved to be hydatid disease based on per-operative and serological findings. Although hydatid disease is a common condition but it rarely involves cervical spinal cord. High index of suspicion is necessary for prompt diagnosis and early management of a treatable cause of spinal cord compression.